Regulatory principles of interpretation in the intellectual thought of Abū Hāmid al-Ghazālī: an uṣūlī study - Suleiman, Hassan (IIUM Press, 2025)
The apparent text (naṣṣ ẓāhir), and the interpreted (muʾawwal) are two categories of the expressed meaning (al-manṭūq) according to al- Imām Abū Hāmid al- Ghazālī in his usūlī famous work “al- Mustasfā,” and according to al-Imām al- ‘Āmidī in his book “al- Iḥkām,” and other scholars of Usūl al- Fiqh. What is the nature of the interpretation attributed to the expressed meaning of the text (manṭūq al-naṣṣ), and what are its regulatory principles (ḍawābiṭ) according to Abū Hāmid al- Ghazālī? This is the subject of this study. The significance and objective of the study lie in the fact that the issue of interpretation raises clear problems and implications for experts or students of Islamic legal theory, as it often involves explaining the text in a way other than its apparent (ẓāhir) meaning. Therefore, the importance of clarifying the concept of interpretation (ta’wīl) among the usūlī scholars, especially Imām al- Ghazālī, and outlining its regulatory principles (dawābit), become evident. This paper aims to present a clear methodology to address the issues of interpretation and regulate its understanding and application. The problem of this study centers around clarifying the nature of interpretation (ta’wīl) according to Imām al- Ghazālī and defining its dawābit by answering several questions which includes: What is the concept of interpretation?; What are its boundaries?; What are the regulatory principles (ḍawābiṭ) for interpretation according to al- Ghazālī?; What are the consequences of excessive interpretation (takalluf) discussed by al- Ghazālī?; What is the degree of agreement and disagreement between al- Ghazālī and other scholars of Usul al-Fiqh?; What are the areas of application of interpretation in the academic field that al- Ghazālī focused on in his books? To find the answers to the aforementioned questions, the study adopts inductive, analytical, and descriptive methodologies, gathering al- Ghazālī’s statements on interpretation and analyzing them to reach an accurate description of the nature and content of interpretation, and then establishing the specific dawabit for the term “interpretation (ta’wīl)” according to him. The research identified the concept of interpretation and its ḍawābiṭ according to al-Ghazali. He demonstrated that it is the conversion of a word from its apparent meaning to a meaning supported by evidence. He also emphasized that interpretation is not permissible in definitive, decisive texts. He also emphasized that the interpretation of linguistic phenomena must conform to the speaker's custom and be subject to precise ḍawābiṭ and conditions. The correct meaning can only be arrived at through strict adherence to the standards of language and Islamic texts, in order to avoid falling into unsound interpretation